Manajemen Program Pengenalan Makanan Khas Daerah Sebagai Media Internalisasi Nilai Pancasila Dalam Kurikulum Merdeka di TK Kelurahan Sokanegra - wijayanti, Catur Menik; Ardy Wiyani, Novan (Generasi Emas, 2024)
Introducing culture to children provides education about the diversity of cultures that should be respected, ensuring that the norms and cultural values of the nation can be passed down to the next generation. The Strengthening Student Profile of Pancasila project aims to embody the government's vision of educational outcomes, demonstrating the character and competencies expected of students throughout and after their learning journey in educational institutions. This research is a descriptive study using a qualitative research approach. The data collection techniques employed in this study include interviews, observations, and documentation. To obtain valid data, the researcher conducted data triangulation. The program of introducing regional culinary specialties as a means of internalizing Pancasila values aims to appreciate diversity. Traditional regional cuisine plays an important role in Indonesian culture. Within the values of Pancasila lies the teaching of respecting differences, including the unique regional cuisines. The materials in this program begin with watching a video on how to make "gethuk" to visualize the process of making it. Afterwards, students will be introduced to the main ingredient used in making "gethuk," which is cassava. Managing the program of introducing regional culinary specialties can serve as a means of internalizing Pancasila values in the independent curriculum, proving to be quite effective. Introducing regional culinary specialties can serve as a platform to familiarize students with cultural diversity and the values inherent in the local community. Keywords: management, food, Pancasila